Ionic Liquids and Salts from Ibuprofen as Promising Innovative Formulations of an Old Drug. (10th April 2019) - Santos, Miguel M.; Raposo, Luís R.; Carrera, Gonçalo V. S. M.; Costa, Alexandra; Dionísio, Madalena; Baptista, Pedro V.; Fernandes, Alexandra R.; Branco, Luís C.
Abstract: Herein we report the synthesis of novel ionic liquids (ILs) and organic salts by combining ibuprofen as anion with ammonium, imidazolium, or pyridinium cations. The methodology consists of an acid–base reaction of neutral ibuprofen with cation hydroxides, which were previously prepared by anion exchange from the corresponding halide salts with Amberlyst A‐26(OH). In comparison with the parent drug, these organic salts display higher solubility in water and biological fluids and a smaller degree of polymorphism, which in some cases was completely eliminated. With the exception of [C16 Pyr][Ibu] and [N1, 1, 2, 2OH1 ][Ibu], the prepared salts did not affect the viability of normal human dermal fibroblasts or ovarian carcinoma (A2780) cells. Therefore, these ibuprofen‐based ionic liquids may be very promising lead candidates for the development of effective formulations of this drug. Abstract : Faster formulations : Ibuprofen‐based ionic liquids and organic salts were prepared with ammonium, imidazolium, and pyridinium cations. Depending on the cation–anion combination, room‐temperature ionic liquids or solid organic salts were obtained with decreased polymorphism or in a complete amorphous state. An enhancement in the solubility of such salts in water and phosphate‐buffered saline in comparison with the neutral or sodium salt was observed, alongside low toxicity toward healthy human cells and ovarian cancer cell lines.